Local Wisdom-Based Environmental Education in Higher Education: Implementing Siri’ na Pacce Values through Community Service - Nur Aqila; Aida Marsugo; Ihwan Ridwan; Qanita Fidelma; Nurhayati Muhitha; A. Hasdiansyah (Prodi PGSD Unsultra, 2026)
The issue of low environmental awareness and behaviour in higher education institutions requires an educational approach that is not only technical in nature, but also rooted in local cultural values. Muhammadiyah University Parepare, as a campus that promotes the slogan Bugis Mendunia (Bugis Goes Global), is committed to internalising Bugis local wisdom values in creating an environmentally friendly campus. This Community Service activity aims to implement the Bugis Heritage Course through environmental education based on Siri' na Pacce values for the academic community of Muhammadiyah University Parepare. The implementation method uses an educational-participatory approach combined with training and awareness through the creation of educational video media. The stages of the activity included planning, production, post-production, and dissemination of the video to students, lecturers, and educational staff. The results of the activity showed that educational videos based on Bugis local wisdom were able to become a contextual and relevant awareness-raising medium for campus life. The main output in the form of educational videos contributes to increasing the academic community's understanding of environmental awareness as a moral responsibility, personal honour, and social empathy. In addition, this activity strengthens the role of students as educational facilitators and agents of change in building an environmentally friendly campus culture. This PkM activity has the potential for sustainability through the use of educational media in lectures and other campus activities, so that the values of Bugis local wisdom can continue to be actualised in a sustainable manner.